Cold hearths and barren slopes - "Agarwal, Bina." (New Delhi, 1986)
This book is a substantially revised and updated version of a research monograph written in 1980, when I spent a year as a Research Fellow at the science policy Research Unit (SPRU), University of Sussex, UK. At that time the woodfuel issue was still relatively unresearched, and I had to depend a good deal on emerging unpublished material.
Keywords: Energy